"Better red than dead": Socialism in British Public Schools, 1900–1918. Issue 2 (13th June 2021) - Makarchev, Nikita; Xiao, Chelsea C.
Abstract: This paper examines socialism in Edwardian public schools. It concentrates on understanding their students' responses to, and conceptions of, socialism's core tenets. For, existing scholarship has depicted these Edwardian institutions as almost uniformly conservative and proficient in inculcating students with pro‐social hierarchy, anti‐social innovation views. Any ideological tensions, then, stemmed from the interaction of popular, conservative‐compliant, dogmas within school contexts: social Darwinism, imperialism, athleticism, muscular Christianity and so on. This paper, however, draws on new Eton College archive sources to enhance and complicate this view. It argues socialism captivated the students' attention and garnered a strong supportive minority that, at times, advocated complete collective ownership. Moreover, the school administration showed tolerance to even the most outspoken socialists, and its non‐hegemonic, semi‐decentralized nature gave rise to local, independent sites of support. Accordingly, this research is important to understanding Edwardian public school ideologies and socialization processes. In wider terms, too, it casts insight on Edwardian socialism's penetration into secondary education and inter‐class acceptance.